IMPLEMENTASI SISTEM PEMANTAUAN DAN PENGENDALIAN SUHU KANDANG AYAM TERTUTUP BERBASIS IOT DI KELURAHAN WONOLOPO KECAMATAN MIJEN KOTA SEMARANG - Supriyanto, Eko; Abu Hasan, Abu; Bramantyo, S.T., M.,T, Hutama Arif; Pramuji, Tulus (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
This Community Service (PKM) provides solutions and innovations regarding the implementation of a temperature monitoring and control system in a closed chicken coop with a capacity of 12,000 broiler chickens in Wonolopo Village, Mijen District, Semarang City. This activity was carried out with the target of this program being broiler chicken breeders, namely Ikhsan chicken coop owners, and community groups. The main problem with Ikhsan broiler cage farming is that temperature measurement and operation of control equipment still need to be revised. The inability to monitor and control the temperature in the cage automatically and continuously causes low cage performance. The still high death rate of chickens due to illness due to hot temperatures in the coop (heat stress) is one of the causes of crop failure or high FCR (Feed Conversion Ratio) or less than optimal productivity so that the performance value achieved is no more than 350. For this reason, system implementation is essential. Monitoring and controlling the temperature of the chicken coop is closed and can be monitored via the internet network. This service aims to provide training and assistance in implementing a closed chicken coop temperature monitoring and control system. With this system, farmers can monitor and control the temperature of the broiler chicken cage at any time, even though they are outside the cage, by utilizing the internet network via their smartphone. This temperature monitoring and control system will increase chicken production.